(untitled) - Buglear, John (Amsterdam, 2010)
Stats Means Business is an introductory textbook written for Business, Hospitality and Tourism students who take modules on Statistics or Quantitative research methods. Recognising that most users of this book will have limited if any grounding in the subject, this book minimises technical language, provides clear definition of key terms, and gives emphasis to interpretation rather than technique. Stats Means Business enables readers to: appreciate the importance of statistical analysis in business, hospitality and tourism understand statistical techniques and develop judgement in the selection of appropriate statistical techniques interpret the results of statistical analysis This new edition includes extra content related to Hospitality and Tourism courses, an extension of the interpretation of correlation analysis and a new section on how to design questionnaires. An introductory text and an accessible approach to a difficult subject, Stats Means Business assumes no prior knowledge of statistics and therefore won’t intimidate students Techniques are explained and demonstrated using worked examples and real life applications of theory. Guidance is also given on using EXCEL, Minitab and SPSS Teaching support materials include fully worked solutions for questions in the book, additional review questions and data sets for lecturers to use for tutorials
Keywords: Commercial statistics,Thống kê thương mại